SAR distribution in a phantom bio-medium due to TiO2 loaded metal diagonal horn - Singh S.; Katare K.K.; Singh S.P. (My University, 2025)
This paper presents the simulation study of specific absorption rate (SAR) distribution in a phantom muscle medium due to TiO2 loaded metal diagonal horn antenna. Diagonal horn is a multimode horn antenna in which the internal fields consist of a superposition of the orthogonal TE10 and TE01 modes in square waveguide. In diagonal horn, excited electric field is parallel to one of its diagonals, causing diagonal polarization of the aperture field. The metal diagonal horn is filled with titanium dioxide (TiO2) to provide good impedance match between the horn and phantom muscle medium (εr = 47.5, tanδ = 0.28421, δ = 1.838 S/m). Metal diagonal horn is designed and simulated at 2.45 GHz using FEM based Ansoft HFSS software for hyperthermia applications. The antenna return loss, distribution of electric fields within the antenna structure, and the SAR distribution in the bio-medium due to the antenna are determined at 2.45 GHz. © 2013 IEEE.